Acute cardiovascular effects of ethanol A controlled non-invasive study. Issue 2 (February 1983) - Kupari, M
Abstract : The acute cardiac effects of ethanol (1 g/kg orally within 60 minutes) were examined in 22 healthy volunteers (11 men and 11 women) by M-mode echocardiography and systolic time intervals for three hours after beginning ingestion. Each subject also took part in a control study, in which the same volume of juice was substituted for ethanol. Heart rate increased by 15% and cardiac output by 17% during ethanol intake, while total peripheral resistance decreased by 15%. Left ventricular end-diastolic diameter was shortened by 2% during the declining phase of blood ethanol concentration; stroke volume and circumferential wall stress were simultaneously decreased by 7% and 5%, respectively. No ethanol-related changes were noted in echocardiographic indices of left ventricular function, neither were any sex differences observed in the cardiovascular changes after ethanol ingestion. Each of the systolic time intervals was significantly altered even during the control experiment. The responses of each of these intervals to ethanol differed significantly from those in the control test as well. Notably, the pre-ejection period/ejection time ratio rose after ethanol, this change, according to simultaneous echocardiographic data, resulting from reduced preload instead of impaired contractility, as maintained in previous investigations. It is concluded that alcohol in modest doses is capable of altering each of the extramyocardial influences on left ventricular function--heart rate, preload, and afterload--but does not impair myocardial performance, at least in normal subjects.